Modulatory effect of Picralima Nitida on oxidative stress: Cobalt, thiol, total protein in Drosophila melanogaster exposed to lead - Osunbor, J.O. Osakue, J.E. (Sokoto Journal of Medical Laboratory Science)
Drosophila melanogaster, commonly known as fruit fly, vinegar fly, is a small model organism used in the study of various disciplines. D. biochemical, neurological and physiological sim ilarities with human beings and has about 75% functional homologs of genes causing diseases in humans. Picralima nitida is a diseases in humans. Picralima nitida is a therapeutic herb used in ethnomedicine for the management of several disease conditions. Theobjective of this study is to induce oxidative stress in Drosophila melanogaster using lead and determine its effect on the levels of selected oxidative stress parameters. Determining the potential modulatory effect of Picralima nitida on selected oxidative stress parameters in lead-induced oxidative stress in Drosophila melanogaster was also known in this study. The phytochemicals of Picralima nitida, and survival rate in Drosophila melanogaster exposed to different concentrations of lead and/or Picralima nitida in meal were also studied. A total of 250 Drosophila melanogaster flies were seen in each of the 9 groups (A-I). Group A was used as the control group and was fed with normal standard meal with water only. Group B were fed with 0.25mg/dl lead acetate meal, group C were fed with 1mg/dl lead acetate meal, group D were fed with 10mg/kg Picralima nitida meal, group E were fed with 100mg/kg Picralima nitida diet, group F were fed with 0.25mg/dl lead acetate and 10mg/kg Picralima nitida diet, group G were fed with 1 mg/dl lead acetate and 10mg/kg Picralima nitida diet, group H were fed with 0.25mg/dl lead acetate 100mg/kg Picralima nitida meal and group I were fed with 1mg/dl lead acetate and 100mg/kg Picralima nitida diet. After about 5 days, flies were homogenized and the supernatant recovered were then used for the various biochemical and survival assay, Cobalt was determined with inductively coupled plasma - mass spectrometry, total protein was determined with Lowrys method and total thiols was determined with Ellman's method. The results showed that lead at various concentrations had a toxic effect on the level of oxidative stress parameters (cobalt, thiols, total protein) in Drosophila melanogaster. While Picralima nitida a medicinal plant had a modulatory effect on the level of oxidative stress parameters (Cobalt, total thiols, total protein) in lead- induced Drosophila melanogaster, although it can become toxic when taken in high concentration. All varying concentrations of lead acetate or/and Picralima nitida reduced the survival rate in the flies. From this study it could be deduced that at low concentration Picralima nitida has modulatory effect on oxidative stress.